A magnetically modified black phosphorus nanosheet-based heparin delivery platform for preventing DVT accurately. Issue 40 (24th September 2019) - Ouyang, Huan; Zheng, Zhuli; Chen, Yutong; Liu, Yu; Hong, Can; Zhu, Yanglong; Deng, Jianjian; Ding, Xingwei; Zhou, Weimin; Wang, Xiaolei
Abstract : A new heparin targeting delivery platform was developed based on iron oxide (Fe3 O4 ) nanoparticles and polyethyleneimine (PEI) functionalized black phosphorus nanosheets (BP NSs). Abstract : A new heparin targeting delivery platform was developed based on iron oxide (Fe3 O4 ) nanoparticles and polyethyleneimine (PEI) functionalized black phosphorus nanosheets (BP NSs). Both in and ex vivo studies suggested that this drug delivery platform (PEI/Fe3 O4 @BP NSs) possessed high heparin loading capacity (≈450%), accurate magnetic enrichment capacity, and good biocompatibility. With the aid of near-infrared (NIR) laser irradiation, this BP NS based delivery platform could further enhance the photothermal thrombolysis effect. Most importantly, the experiments in vivo confirmed that the proposed PEI/Fe3 O4 @BP NSs could considerably prolong the effective drug concentration duration of heparin. By which means, accurate, long-acting, and effective thromboprophylaxis could be accomplished with limited drug dosage, which could radically reduce the perniciousness of drug overdose.